Frequency of Complications Following Cataract Surgery in Diabetic Patients at Tertiary Care Hospital - Muhammad Bilal; Shafqat Ali Shah; Marina Murad; Saad Ali; Ammad Ali; Muhammad Ayub (Gandhara University, 2022)
OBJECTIVES: To determine the frequency of complications following cataract surgery in diabetic patients admitted in the ophthalmology unit. METHODOLOGY: A prospective descriptive interventional case series study was conducted after approval of the ethical committee, from June 2017-June 2020 at the Ophthalmology department MTI-MMC. A total of 129 patients from either gender were enrolled in study. All the study patients went through detailed history and complete ocular examination. After necessary investigations, surgical procedure was carried out. Results were analyzed through the SPSS-24 version. RESULTS: Out of the total 129 eyes of the diabetic patients, fifty-nine (45.7%) were males and seventy (54.3%) were females with a ratio of 1:1.2. Uveitis leads the chart in complications found in twenty (15.50%) eyes while PODR being the least common found in only ten (7.75%) eyes. Worse visual acuity was observed in fourteen (10.85%) eyes. Striate keratopathy and posterior capsule opacification were found in sixteen (12.40%) and fifteen (11.62%) eyes respectively. Among the patients, 15.7% were having more than one complication during follow-up visits and eighty-eight (68.2%) eyes were found to have none complication. The age group 51-60 years observed frequent complications as compared to other groups. Similarly female gender (38.57%) has frequent complications as compared to males (2.7%). CONCLUSION: The study concludes Uveitis as the most common complication observed in 15.50% 0f the eyes while worse visual acuity (10.85%) and progression of diabetic retinopathy (7.75%) being the least common. Striate keratopathy was found in 12.40% while posterior capsule opacification in 11.62% of the eyes.